Evaluation of Human Errors Using Standardized Plant Analysis Risk Human Reliability Analysis Technique among Delivery Emergency Nurses in a Hospital Affiliated to Tehran University of Medical Sciences - Fateme Tanha; Adel Mazloumi; Vahdat Faraji; Zeinab Kazemi; Mina Shoghi (Tehran University of Medical Sciences, 2015)
Background: Recently, considerable attention has been paid to medical errors in health care system. Taking into account that nurses spend more time with patients in comparison with other staff, they are more prone to human errors. The present research conducted to investigate nurseschr('39') errors in delivery emergency ward in a hospital affiliated to Tehran University of Medical Sciences. Material and Methods: In the present coss-sectional study,at first, task analysis was conducted  to nursing proffession using Hierarchical Task Analysis (HTA) technique by FGD. In next step, the Human Error Probability (HEP) was determined utilizing SPAR-H method and dependences of performance-shaping factors (PSFs) and action and diagnosis activities were identified. Finally, after determinig dependency level, the final diagnosis HEP was calculated and risk assessment level was carried out  using the riskschr('39') probability and intensity tables. Results: According to the results, four groups of studied tasks, the lowest errors were belonged to "working with serum pumping machinechr('39')chr('39') subtask with the error level of 0.055 and the highest error probability related to chr('39')chr('39') transfusion of blood productschr('39')chr('39') subtask with the error rate of 0.78. Moreover, special responsibilities of the wards had the highest level of undesirable risks. Conclusion: In the present study, the analysis of identified errors reveals due to high work demand, insufficient time and the need for accurate administrative monitoring and providing required arrangements, the main causes of errors can be attributed to high level of stress and complexity in the tasks of delivery emergency ward.